Characterization of newborns with moderate or severe perinatal asphyxia managed with selective cerebral hypothermia in the newborn unit of the Hospital Universitario San Ignacio from june 2015 to march 2017 (2019)
Introduction: Hypoxic- ischemic encephalopathy generates various alterations in the central nervous system of the newborn, with various consequences ranging from physical and mental disability to death. The evidence indicates that moderate to severe hypox